2015
DOI: 10.1002/alr.21552
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric computed tomography analysis of the olfactory cleft in patients with chronic rhinosinusitis

Abstract: Background Commonly used computed tomography (CT) staging systems for chronic rhinosinusitis (CRS) focus on the sinuses and do not quantify disease in the olfactory cleft. The goal of the current study was to determine whether precise measurements of olfactory cleft opacification better correlate with olfaction in patients with CRS. Methods Olfaction was assessed using the 40-item Smell Identification Test (SIT-40) before and after sinus surgery in adult patients. Olfactory cleft opacification was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 26 publications
4
57
3
1
Order By: Relevance
“…As a result, the literature regarding correlation of these CT scoring systems and patient-reported outcomes has been mixed 8 . Interestingly, more recent studies using semi-automated volumetric analysis of CT scans have shown a higher degree of association with symptoms 9,10 , suggesting that more comprehensive methods of CT image analysis may be important for linking symptoms with objective measures of inflammation. These methods, however, are time-consuming and may not be practical for routine clinical use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the literature regarding correlation of these CT scoring systems and patient-reported outcomes has been mixed 8 . Interestingly, more recent studies using semi-automated volumetric analysis of CT scans have shown a higher degree of association with symptoms 9,10 , suggesting that more comprehensive methods of CT image analysis may be important for linking symptoms with objective measures of inflammation. These methods, however, are time-consuming and may not be practical for routine clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, a CNN is a biologically-inspired computer algorithm that uses thousands of simple units, modeled after neurons, that take an input from one layer of units, perform a mathematical transformation, and feed the output to the next set of neurons. Similar to their biological counterparts, while each individual neuron is simple to understand, structured networks of them have demonstrated complicated, emergent properties that are useful for pattern-recognition tasks 9,10 . These algorithms have been used to great effect in multiple applications 11 , most notably the ImageNet challenge, an annual international computer vision competition that asks computer scientists to develop algorithms to classify a given set of images into over 1,000 categories.…”
Section: Introductionmentioning
confidence: 99%
“…Productivity loss from CRS rivals that of other chronic disease processes such as asthma, diabetes, and heart diseases [15, 16]. CRS is typically classified into 2 types: CRS with nasal polyps (NP) and CRS without NP [17-19]. Clinical features of CRS with NP with eosinophil-dominant inflammation as “eosinophilic CRS (ECRS)” were first reported in Japan in 2001 [20].…”
Section: Introductionmentioning
confidence: 99%
“…1820 However, in CRS patients who already demonstrate a decreased quality of life, it appears that olfactory dysfunction does not have an additional negative additive effect. 21 Among patients with CRS, those with nasal polyposis, eosinophilia, asthma, smoking, and increased age are more likely to demonstrate decreased olfactory function.…”
Section: Introductionmentioning
confidence: 99%